Pengaruh Besar Arus Pengelasan Terhadap Harga Integral J Pada Baja ST 52. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Kawasan dan Pedesaan Universitas Gadjah Mada, 1999)
ABSTRAK Fracture toughness of welded plate has been investigated.Parameter used in this investigation is welding current.The base material in this experiment is ST 52 steel, and OK 7575 electrode. The ST 52 steel plate is welded with OK 7575 electrode and 110A, 120A, 130A welding current. Specimen of welded plate is CT specimen.ln this experiment J integral is tested with Servopulzer testing machine. Single speciment testing is used to find J integral. The result of this experiment shows that, welding current effects J integral the highest value of J1 is given by 130 A welding current. Key word: